Salmonella enterica adhesion: Effect of Cinnamomum zeylanicum essential oil on lettuce. (August 2019) - Rossi, Chiara; Chaves-López, Clemencia; Možina, Sonja Smole; Di Mattia, Carla; Scuota, Stefania; Luzzi, Ida; Jenič, Teja; Paparella, Antonello; Serio, Annalisa
Abstract: Salmonella is a foodborne pathogen able to adhere and persist on biotic and abiotic surfaces, including vegetables, which are even more linked to foodborne outbreaks. In this work, first we investigated the capability of Salmonella to adhere on different surfaces (stainless steel, polypropylene and lettuce), then we evaluated the potential effect of essential oils in reducing the adhesion and persistence of the pathogen on lettuce. Eight essential oils (EO) were tested on five Salmonella enterica strains (serovars Derby, Thompson, Napoli, Kasenyi and Veneziana). Cinnamomum zeylanicum EO (CEO) was the most effective, according to Minimal Inhibitory Concentration (MIC 1.25–1.87 μL/mL) and to growth/inhibition dynamics. To simulate real conditions, a cocktail of Salmonella Kasenyi, S . Veneziana and S . Napoli was applied on the three surfaces, but it adhered only on lettuce, starting from 1 h of contact (4.59 ± 0.34 Log UFC/cm 2 ). Five μL/mL CEO, applied on lettuce, immediately reduced the loosely and strongly attached cells (reduction of 0.78 Log and 0.63 Log CFU/cm 2, respectively), with significant effect up to 120 h. CEO also inhibited the Polyphenol Oxidase activity, thus preserving lettuce colour during storage. Cinnamon EO could therefore help to improve safety and appearance of fresh-cut lettuce during storage. Highlights: Salmonella adhesion was tested on three different surfaces (LDs, SSCs, PPCs). Cinnamomum zeylanicum (CEO) was the most effective essential oil against Salmonella . CEO reduced strong and loose attachment of Salmonella on lettuce leaves. CEO reduced Polyphenol Oxidase activity in lettuce, reducing the Browning Index. CEO could be potentially applied as washing treatments of lettuce.